Self-care behavior and social support among persons with hypertension at Sher-E-Bangla Medical College Hospital in Barishal, Bangladesh - Rani, Krishna; Akter, Halima; Gharami, Tumpa (Journal of Midwifery and Nursing, 2025)
Hypertension, a major global public health issue, affects millions worldwide and is defined as persistently elevated blood pressure (?140/90 mmHg) on two or more occasions. Globally, the prevalence of hypertension surged from 594 million in 1975 to 1.13 billion in 2015. In Bangladesh, the prevalence has risen alarmingly from 16% in 2012 to 35.6% in 2014, with an average prevalence of 12.2%. This study explores self-care behaviors and social support among 183 hypertensive patients at Sher-e-Bangla Medical College Hospital, Barishal. Using the Hypertension Self-Care Behavior and Perceived Social Support scales, lifestyle modifications and social support levels were assessed. Results revealed low self-care practices (M = 2.22, SD = 0.22) and moderate social support (M = 5.74, SD = 1.03). Significant differences in self-care behaviors were associated with gender (p = 0.04), living status (p = 0.01), family history (p = 0.000), comorbidities (p = 0.01), and stress management (p = 0.000). Social support varied significantly with income (p = 0.007), family type (p = 0.01), and comorbidities (p = 0.000). These findings highlight critical demographic factors influencing hypertension management. Tailored interventions addressing self-care and enhancing social support are essential for improving health outcomes among hypertensive patients.